Undisciplining Social Science: Wittgenstein and the Art of Creating Situated Practices of Social Inquiry. (22nd January 2015) - Shotter, John
Abstract: There are now countless social scientific disciplines—listed either as the science of … X …  or as an ‐ology of one kind or another—each with their own internal controversies as to what are their "proper objects of their study." This profusion of separate sciences has emerged, and is still emerging, tainted by the classical Cartesian‐Newtonian assumption of a mechanistic world. We still seem to assume that we can begin our inquiries simply by reflecting on the world around us, and by allowing our conceptualizations to guide our actions in our inquiries. Beginning our inquiries in this retrospective manner, however, means that our concepts and conceptualizations are both after‐the‐fact and beside the point, for 'something else' altogether is guiding us in the performance of our situation‐sensitive actions than merely our conceptualizations. We need before‐the‐fact, hermeneutically‐structured inquiries that can 'set out' inner 'landscapes of possibilities', to think‐with and to provide guidance, as we try in our more scientifically organized efforts to achieve socially desired outcomes in particular socially shared situations. Conducting such preliminary inquiries is thus an art, requiring not only judgment, but also imagination and poetic forms of expression aimed at creating such shared, inner landscapes among all concerned.